Characterizing the evolution of lesion, penumbra and blood-brain barrier permeability in a photothrombotic juvenile rat stroke model using MRI and histology - Trish Domi; Faraz Honarvar; Daniel Sare; Mahmoud Slim; Nomazulu Dlamini; Andrea Kassner (Scientific Reports)
Abstract Pediatric stroke is a significant cause of childhood mortality and morbidity. The clinical research in this field bears certain limitations that do not exist in the pre-clinical setting. Experimental models of ischemic stroke show differences in lesion evolution and blood-brain barrier (BBB) permeability between adult and neonatal rats. However, little is known about these factors in the juvenile stage. Here, we characterize the evolution of the lesion, penumbra and degree of BBB permeability in a photothrombotic ring model of juvenile stroke using a mixed longitudinal and cross-sectional study. Fourteen Sprague Dawley juvenile rats (weight 130–189 g), lesion, penumbra volume and blood-brain barrier (BBB) leakage were measured longitudinally on days 0, 2, and 7 following photothrombotic stroke. Magnetic resonance imaging (MRI) techniques were used to measure lesion and penumbra volumes (T2-weighted imaging [T2]), water restriction (diffusion-weighted imaging [DWI]) and BBB leakage (with dynamic contrast-enhanced imaging [DCE]). To confirm stroke, histology was performed (n = 9) with Triphenyltetrazolium chloride staining (TTC) (n=9), (Haemotoxylin and Eosin (H&E) staining (n=3); andn Evans Blue (EB) staining to assess BBB permeability (n=9). We found the volume of the penumbra to be larger and better delineated on MRI and histology in the acute compared to the subacute and chronic stages. The lesion was smaller in volume and increased over time following same time trajectory. The BBB was most compromised at the hyperacute stage (day 0) and decreasingly, yet persistently, disrupted to day 7. Our in vivo and ex vivo findings provide insight into the evolution of stroke and could serve as a study model to test blood-brain barrier stabilization agents in the pediatric setting.